Multi-Criteria Analysis to Map Malnutrition Vulnerability to The Impact of Climate Change in West Sumatra, Indonesia - Defriani Dwiyanti; Eri Barlian; Abdul Razak; Indang Dewata; Nurhasan Syah; Dewi Rahmadani Siregar (YCAB Publisher, 2026)
Background: Indonesia is the world's second most disaster-prone country and faces significant climate change impacts. West Sumatra has high malnutrition, moderate food insecurity, and disaster risk. Mapping climate vulnerability is critical for mitigation and adaptation. Objective: Building on this need, this study aims to map the vulnerability of malnutrition due to climate change in West Sumatra Province, Indonesia. Methods: The research employed an analytical descriptive approach, utilizing secondary data from official agencies. Sources included the Central Statistics Agency of West Sumatra Province, the Meteorology, Geophysics and Climatology Agency, the Indonesian Nutrition Status Survey, and the Indonesian Health Survey from 2019 to 2023. The data covered three vulnerability indicators: exposure, sensitivity, and adaptive capacity. These were analyzed by the Weighted Product method and classified into five categories of vulnerability (very low, low, medium, high, very high) using the Equal Interval method. Results were presented as thematic maps using ArcGIS software. Results: The analysis revealed that 5.3% of areas had very high vulnerability to malnutrition linked to climate change. Meanwhile, 10.5% were high, 26.3% medium, 42.1% low, and 15.8% very low. The coastal regions of Mentawai, West Pasaman, and South Coast were the most vulnerable. Vulnerability was determined by exposure, sensitivity, and adaptive capacity. Regions with higher vulnerability had greater sensitivity and lower adaptive capacity. Regions with lower vulnerability showed better adaptive capacity. Conclusions: Based on the findings, it is recommended to prioritize areas with high and very high vulnerability. Efforts should be focused on improving access to health and nutrition services, empowering women in household food decisions, and strengthening food systems to strengthen regional adaptive capacity. Keywords: mapping; vulnerability; malnutrition; climate change